Pengaruh Akuntabilitas Dan Transparansi Terhadap Pengelolaan Bantuan Langsung Tunai Dana Desa Dengan Sistem Pengendalian Internal Sebagai Variabel Moderasi Di Kabupaten Gowa - Adrianti, Adrianti; Sumarlin, Sumarlin; Anwar, Puspita Hardianti (Income Journal: Accounting, Management and Economic Research, 2023)
The purpose of this study was to find out how accountability and transparency influence the management of direct assistance to disburse village funds with an internal control system as a moderating variable in Gowa Regency. The data used in this research is primary data collected through a direct questionnaire survey. Data analysis used multiple linear regression analysis and moderating regression analysis with the absolute difference value approach. The number of respondents used in this study were 150 people. Respondents in this study were all village officials in Bontonompo District. The results of this study indicate that accountability has a positive and significant effect on the management of BLT Dana Desa. Transparency has a positive and significant effect on the management of the Village Fund BLT. The internal control system does not moderate the effect of accountability on the management of the Village Fund BLT. The internal control system moderates the effect of transparency on the management of the Village Fund BLT.